ALTERNATIF STRATEGI PEMBELAJARAN SELAMA PANDEMI COVID-19 DI STAI SUMATERA MEDAN - Rahmat Rifai Lubis; Nana Mahrani; Leni Masnidar Nasution (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
This study aims to analyze the various learning strategies applied by the lecturers of the Prodi PAI STAI Sumatra Medan Study Program online learning, (2) the obstacles faced by the lecturer in implementing these learning strategies. The method used for this research is a qualitative method based on descriptive studies. With the number of respondents as many as 9 people, in this case, specifically in the Prodi PAI. The research results (1) Some of these learning strategies include assignment-based learning strategies, project-based learning strategies, literacy-based learning strategies, online discussions. However, from its application there are several obstacles, namely as follows: network and internet package constraints, difficulties in implementing learning steps, difficulties in guiding the implementation of learning with the strategies applied.